2019
DOI: 10.18280/ts.360609
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet-Based Self-adaptive Hierarchical Thresholding Algorithm and Its Application in Image Denoising

Abstract: This paper attempts to construct a suitable wavelet for image denoising based on wavelet thresholding algorithm. First, the author discussed how image thresholding is affected by the wavelet orthogonality and bi-orthogonality, the features of vanishing moments and the odd or even symmetry of the decomposition end filter. The discussion shows that the most desirable wavelet for image denoising is the biorthogonal wavelet, in which the decomposition end filter has zero point even symmetry, the low-pass decomposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…In 2019, Zhao [11] bstudied an improved SFA algorithm based on visual invariance, and applied it to extract features of natural images, which achieved good results. The study confirmed the invariance of slow features and slow structures in the visual space, and the proposed algorithm proved to have good anti-noise capacity [12]. In 2020, Zhao [13] studied an improved SFA algorithm based on visual selectivity, and applied it in the feature extraction of limited defocused image sequences, which achieved good results.…”
Section: Introductionmentioning
confidence: 70%
“…In 2019, Zhao [11] bstudied an improved SFA algorithm based on visual invariance, and applied it to extract features of natural images, which achieved good results. The study confirmed the invariance of slow features and slow structures in the visual space, and the proposed algorithm proved to have good anti-noise capacity [12]. In 2020, Zhao [13] studied an improved SFA algorithm based on visual selectivity, and applied it in the feature extraction of limited defocused image sequences, which achieved good results.…”
Section: Introductionmentioning
confidence: 70%
“…Feature extraction is one of the important pre-processing steps in the classification process. Wavelet transform [13,14], ridgelet transform [15], ripplet transform [16], histogram of the gradient [17,18], and local binary pattern (LBP) are some of the many known feature extraction methods. By using these methods, edges, orientation, volume, resolution, and histogram are obtained from the images [19,20].…”
Section: Feature Extractionmentioning
confidence: 99%
“…The traditional image denoising methods mainly include mean filtering [9], median filtering [10] and wavelet transform [11], which are insufficient because they have poor robustness in the real world and cannot accurately and efficiently remove noise from images [12]. With the development of deep learning, image denoising algorithms based on deep learning have been widely used due to their efficient and convenient characteristics and have become an effective solution to deal with image denoising.…”
Section: Introductionmentioning
confidence: 99%
“…where GELU belongs to the class of activation functions, and We use the feed-forward module (FFM) to enhance the nonlinear expression of FFCA. The computational procedure is shown in Equation (11):…”
Section: Feed Forward Network Introductionmentioning
confidence: 99%